MPD BUKAN ADVOKAT PARA NOTARIS BERDASARKAN UNDANG-UNDANG NO.30 TAHUN 2004 TENTANG JABATAN NOTARIS - Aryani Witasari (Unissula, 2012)
Notary is apublic official who runs most of the public functionsin the state, especially in the civil law. Notary has authority to make authentic certificate of all deeds, agreements, and regulations which is obligated by legislation or which is desired by an interested party, to be declared in the deed authentic, guaranteeing deed date, saving certificates, giving grosse, copies and citations of certificates, all along the deed is not assigned or excluded to the officer or other person which is specified by law.In the authority need to carry out surveillance and MPD is the only aut horized institution to implement surveillance, inspection and giving punishment toward notaries in the district/city. The institution exists of Region Supervisor Council and the Central Supervisors Council.MPD has a special authority which can be run to check notary relate to the investigators request, prosecutors or judges to take a photocopy minuta or other documents which is attached to the minuta or protocols in Notary storage, calling the Notary related to deed which has been made or notary protocols which are in Notary storage.Keywords: Notary, MPD, Lawyer